2012
DOI: 10.1002/ptr.4614
|View full text |Cite
|
Sign up to set email alerts
|

Rhynchophylline Attenuates LPS‐induced Pro‐inflammatory Responses through Down‐regulation of MAPK/NF‐κB Signaling Pathways in Primary Microglia

Abstract: Excessive activation of microglial cells has been implicated in various types of neuroinflammation. Suppression of microglial activation would have therapeutic benefits, leading to the alleviation of the progression of neurodegeneration. In this study, the inhibitory effects of rhynchophylline (RIN), a tetracyclic oxindole alkaloid component isolated from Uncaria rhynchophylla (Miq.) Jacks., on the production of pro-inflammatory mediators were investigated in lipopolysaccharide (LPS)-stimulated microglia. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 26 publications
2
30
0
1
Order By: Relevance
“…Their pharmacological activities were extensively studied which have been shown to exert anti-inflammatory [5456], antioxidative [57, 58], and neuroprotective [57, 5964] effects in CNS. Anti-inflammatory effects of rhynchophylline and isorhynchophylline were found in primary cultured rat cortical microglia.…”
Section: Alkaloidsmentioning
confidence: 99%
See 3 more Smart Citations
“…Their pharmacological activities were extensively studied which have been shown to exert anti-inflammatory [5456], antioxidative [57, 58], and neuroprotective [57, 5964] effects in CNS. Anti-inflammatory effects of rhynchophylline and isorhynchophylline were found in primary cultured rat cortical microglia.…”
Section: Alkaloidsmentioning
confidence: 99%
“…More recently, another study investigated the action of rhynchophylline on the productions of proinflammatory mediators and its potential mechanisms in LPS-activated microglia. The study showed that rhynchophylline reduced the productions of nitric oxide, prostaglandin E2 (PGE 2 ), MCP-1, TNF- α , and IL-1 β [56]. Besides, mRNA levels of inducible nitric oxide synthase (iNOS) and cyclo-oxygenase-2 (COX-2) were also suppressed by rhynchophylline [56].…”
Section: Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the central nervous system, Rhy could be beneficial for memory impairment induced by the dysfunction of cholinergic systems in the brain [4]. Rhy is also effective in sedation, anti-convulsion, anti-epilepsy, and [6][7][8][9][10], thus it is widely used in traditional Chinese medicines prescribed mainly to treat ailments in the central nervous and cardiovascular systems, such as lightheadedness, convulsions, numbness, and hypertension. The molecular structure of Rhy was shown in Fig.…”
Section: Introductionmentioning
confidence: 99%